Digital Transformation Design towards Logistics 4.0 in SME: A Case Study for PT XYZ - Krisna Wardhana; Prio Utomo; Friska Natalia (Conference Series, 2021)
The rapid development of technology and information and communication has a direct impact on the business of the Indonesian people. SMEs are one of the pillars in the economic sector in Indonesia. However, logistics has always been an obstacle to business growth in the SME sector. In Indonesia, logistics costs are still high compared to GDP, which is the background of problems that can be solved by implementing logistics 4.0. This literature will provide input for SME entrepreneurs, who will carry out digital transformation in the logistics sector of their business. The inputs that will be given include the importance of digital transformation in the logistics sector and the benefits that will be provided as a result of digital transformation. By using the digital maturity model for logistics 4.0 concept as a research method, an SME will be able to find its current state and also be able to determine strategies that will help SMEs go to their intended future state. Various analyzes will be carried out to determine the state of the SME business, so that appropriate digital transformation can be carried out regarding the SME logistics current state.